1993
DOI: 10.1007/bf00225001
|View full text |Cite
|
Sign up to set email alerts
|

DNA fingerprinting in sugar beet (Beta vulgaris) — identification of double-haploid breeding lines

Abstract: The distribution and abundance of simple repetitive sequences complementary to the synthetic oligonucleotides (GACA)4, (GATA)4, (GTG)5 and (CA)8 in the genomes of several cultivars of Beta vulgaris and in the wild beet B. vulgaris ssp. maritima were investigated. Hybridization experiments revealed that all four motifs were present, though at different abundances, in the genomes of all of the investigated beet cultivars. Considerable intraspecific variation of the resulting DNA fingerprints was observed. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Moreover, these approaches could not assess the change(s), if any, at the DNA sequence level. During the last few years, molecular markers such as RFLPs (Breiman et al 1987;Chowdhury et al 1994, Shimron-Abarbanell andBreiman 1991;Shirzadegan et al 1991), RAPDs (Bohanec et al 1995;Brown et al 1993;Isabel et al 1993;Rani et al 1995) and oligonucleotide fingerprinting (Poulsen et al 1993;Schmidt et al 1993;Vosman et al 1992) have been found to be of tremendous utility in addressing fundamental and practical questions of plant tissue culture. In the study presented here, we have screened enhancedaxillary-branching-derived Eucalyptus tereticornis and E. camaldulensis plants by RFLP, RAPD, and oligonucleotide fingerprinting markers to assess their genetic fidelity, and to enquire into the applicability of the marker(s) for rapid appraisal of tissue-culture-derived eucalypt plants.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, these approaches could not assess the change(s), if any, at the DNA sequence level. During the last few years, molecular markers such as RFLPs (Breiman et al 1987;Chowdhury et al 1994, Shimron-Abarbanell andBreiman 1991;Shirzadegan et al 1991), RAPDs (Bohanec et al 1995;Brown et al 1993;Isabel et al 1993;Rani et al 1995) and oligonucleotide fingerprinting (Poulsen et al 1993;Schmidt et al 1993;Vosman et al 1992) have been found to be of tremendous utility in addressing fundamental and practical questions of plant tissue culture. In the study presented here, we have screened enhancedaxillary-branching-derived Eucalyptus tereticornis and E. camaldulensis plants by RFLP, RAPD, and oligonucleotide fingerprinting markers to assess their genetic fidelity, and to enquire into the applicability of the marker(s) for rapid appraisal of tissue-culture-derived eucalypt plants.…”
Section: Introductionmentioning
confidence: 98%
“…SSRs are abundant within genomes and are present in both coding and noncoding regions. They are also usually characterized by a high degree of length polymorphism and, for this reason, they have proven to be extremely valuable tools for genome studies in many organisms and very powerful genetic markers that are often specific to single varieties or even individuals (Weising et al 1989;Schmidt et al 1993;Depeiges et al 1995;Schuler et al 1996;Knapik et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet (Beta vulgaris L.; 2n = 2x = 18) is a valuable model species for investigating the large scale organization of the nuclear genome because (i) the genome is relatively small with 758 Mbp (16), (ii) fluorescent in situ hybridization can accurately locate sequences along the metaphase chromosomes and within interphase nuclei (17), (iii) major classes of the repetitive DNA have been characterized including both satellite and retrotransposon sequences (18)(19)(20)(21)(22), and (iv) microsatellites are known to be highly abundant (23).…”
mentioning
confidence: 99%